2021
DOI: 10.1021/acsomega.1c04222
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Dielectric Constant and Surface Engineering of a BaTiO3/Porous PDMS Composite Film for Enhanced Triboelectric Nanogenerator Output Performance

Abstract: In this work, synergistic effects derived from surface engineering and dielectric property tuning were exploited to enhance the output performance of a triboelectric nanogenerator (TENG) based on an inorganic/porous PDMS composite in a contact–separation mode. BaTiO3 (BT)/porous PDMS films with different BT weight ratios were fabricated and evaluated for triboelectric nanogenerator (TENG) application. Maximum output signals of ca. 2500 V, 150 μA, and a power density of 1.2 W m–2 are achieved from the TENG cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…The characteristic peaks assigned to the nonpolar α-PVDF phase are located at 490, 532, 614, 763, 795, 855, 973, 1148, 1212, 1382, and 1423 cm −1 with the most representative intense peaks at 763 and 614 cm −1 , while the peaks specific to the ferroelectric β polymorph reported at 510, 840, 1275, and 1402 cm −1 wavenumbers, as validated in [41,47]. However, the literature reports and our FTIR data have shown that there are also peaks in the range of 870-885 cm −1 , 1171-1182 cm −1 , and 1398-1404 cm −1 which have similar characteristics to the α, β, and γ-phases or to mixed phases [19,[34][35][36][37]41,[54][55][56][57]. The most important bands are specific to the α and β phases, whose formation is dependent on the processing conditions and composition.…”
Section: Phase Composition Analyzed By X-ray Diffraction and Infrared...supporting
confidence: 79%
See 3 more Smart Citations
“…The characteristic peaks assigned to the nonpolar α-PVDF phase are located at 490, 532, 614, 763, 795, 855, 973, 1148, 1212, 1382, and 1423 cm −1 with the most representative intense peaks at 763 and 614 cm −1 , while the peaks specific to the ferroelectric β polymorph reported at 510, 840, 1275, and 1402 cm −1 wavenumbers, as validated in [41,47]. However, the literature reports and our FTIR data have shown that there are also peaks in the range of 870-885 cm −1 , 1171-1182 cm −1 , and 1398-1404 cm −1 which have similar characteristics to the α, β, and γ-phases or to mixed phases [19,[34][35][36][37]41,[54][55][56][57]. The most important bands are specific to the α and β phases, whose formation is dependent on the processing conditions and composition.…”
Section: Phase Composition Analyzed By X-ray Diffraction and Infrared...supporting
confidence: 79%
“…Both values are superior with respect to 0.122 μW/cm 2 reported for the modified BT-PVDF piezoelectric sensor in [ 11 ] or of 1 μW/cm 2 [ 21 ]. They are in the same range as reported for (Ba,Ca)(Ti, Zr)O 3 -PVDF of 16.7 μW/cm 2 [ 86 ], but lower than for hybrid PTENG reported in [ 62 ] for a complex composite formed by hybrid TiO 2 nanosheets with Ag nanoparticles embedded into a polydimethylsiloxane matrix (48 μW/cm 2 ) and with a few orders in magnitude lower than one of the highest power density of 1.21 W/m 2 reported for surface- and pore-engineered BT-polymer composites in [ 34 ]. We may conclude that the present harvesting outputs found in BT-PVDF, and in particular in (Ag-BT)-PVDF hybrid composites produced by a simple wet synthesis method, are very promising and their response can be further improved and optimized.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…As shown in Figure 4 b, in addition to peaks for C (284.8 eV) and O (102.3 eV) [ 40 , 41 ], characteristic peaks for Si can be seen for the PDMS-pCA@CNWF spectrum when compared to those of the CNWF. The peaks at 102.3 eV and 152.0 eV are attributable to Si 2p and Si 2s from PDMS [ 42 , 43 ]. Therefore, these results indicate the successful deposition of PDMS on the pCA@CNWF surface.…”
Section: Resultsmentioning
confidence: 99%